Climate resilient and nutri-smart fruit varieties - Damodaran, T; Yadav, Ashish; Singh, Anshuman; Singh, S K; Dayal, Vishambhar; Kushwaha, Amar Kant (Indian Horticulture, 2026)
Long-term research and advanced breeding strategies on subtropical fruit crops have led to the development of climate-resilient varieties that cater to economic stability, consumer preferences, and industry standards. ICAR-CISH has identified and released several climate-resilient fruit varieties through the State Variety Release Committee (SVRC) of Uttar Pradesh and the Central Variety Release Committee (CVRC), New Delhi, for the Uttar Pradesh region. This paper highlights varieties officially released in 2024 and 2025, exemplifying the institute’s efforts to strengthen the resilience and productivity of subtropical fruit crops.